Geopolitics, Ethnic Conflicts along the Border, and Chinese Foreign Policy Changes toward Myanmar. Issue 1 (2nd January 2017) - Han, Enze
ABSTRACT: Ever since Myanmar reoriented its foreign policy as a result of its transition to democratic rule in 2010, it has significantly improved its relations with the West, particularly the United States. Amid heightened geostrategic competition between the U.S. and China, how can we understand the Chinese government's changing approaches to Myanmar, where China's strategic and economic interests face unprecedented pressure? This article examines those changes in the context of the Chinese government's response to three militarized ethnic conflicts along its border with Myanmar before and after Myanmar's foreign policy reorientation. Drawing evidence from Chinese Ministry of Foreign Affairs statements and Chinese media coverage of the 2009 and 2015 Kokang conflicts and the 2011-2013 Kachin conflict, the article argues that combined geopolitical changes and domestic nationalist signaling explain the variations of China's foreign policy approaches to Myanmar. The article thus contributes to ongoing interest in China's foreign policy approaches to Southeast Asia in the wake of geostrategic competition between China and the United States.